A Quantum Key Distribution Using Optical Frequency Comb Source - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2021)
The use of quantum cryptography aims to perform a secure key exchange, so that agents outside the system are not able to obtain information flowing through the channel. This work proposes the use of a Quantum Key Distribution (QKD) technique, specifically the BB84 protocol, with the objective of randomly generating a key for the encryption of information and distribute it securely afterwards. As a result, the same key is successfully generated at each end of the communication channel, and is never transmitted over it, for which it proposes the use of an Optical Frequency Comb Source (OFCS), seeking to increase the capacity of the optical medium to support more transmitter-receiver pairs (Client-Server) © 2021 IEEE.